Effect of Flooring on Lower Extremity Discomfort during Food Service Tray-line Jobs. (September 2017) - Mahesh, Vishnu; Li, Yueqing; Craig, Brian
This paper investigate the extent to which flooring mats affect stress and fatigue among food service workers on trayline duties. A food service trayline job was simulated in the lab to study the effect of the flooring mat on the lower leg swelling, muscle temperature, fatigue levels and discomfort levels. Six participants participated in the study and performed a 1-hour simulated trayline job. Results showed a significant effect of flooring condition on the muscle temperature change in Tibialis Anterior and Quadriceps with decreasing trend observed for hard floor condition. Results also indicated an increasing trend for leg volume and higher fatigue and discomfort in hard floor condition.